The State of Disability Awareness in American Medical Schools. (September 2017) - Seidel, Erica; Crowe, Scott
Abstract : Abstract: This study was designed to: (1) determine how many American medical schools include disability awareness in their curriculum, (2) explore the format of disability awareness programs in existence, and (3) understand why some schools do not include disability awareness in their curriculum. An online survey was sent to deans of medical education (or equivalent positions) at accredited allopathic and osteopathic American medical schools ( N = 167) in 2015. Seventy-five schools (45%) completed surveys. Fifty-two percent (39/75) reported having a disability awareness program. The most common format was people with disabilities or caregivers speaking in a large group setting. Programs were most likely to focus on adults with physical disabilities. Among schools without a program, the top barriers were no one advocating for inclusion in the curriculum and time constraints. Nearly half of schools without a program expressed interest in adopting an awareness curriculum if one was made available. Such results indicate that efforts should be made to increase the number of schools that provide disability awareness education through increased advocacy and providing additional resources to schools without a curriculum. Abstract : Supplemental digital content is available in the text.